IL-33/ST2 immune responses to respiratory bacteria in pediatric asthma - Hentschke, Isabell; Graser, Anna; Melichar, Volker O.; Kiefer, Alexander; Zimmermann, Theodor; Kross, Bettina; Haag, Patricia; Xepapadaki, Paraskevi; Papadopoulos, Nikolaos G.; Bogdan, Christian; Finotto, Susetta (Scientific Reports, 2017)
Here we investigated the relationship between local bacterial colonization and anti-bacterial immune responses in pre-school asthmatic and control children within the EU-wide study PreDicta. In this cohort of pre-school asthmatic children, nasopharyngeal colonization with Gram-negative bacteria such as Haemophilus influenzae and Moraxella catarrhalis was found to be associated with the highest interferon beta (IFN?) and IL-33 levels in the nasal pharyngeal fluids (NPF). IL33R-ST2 was found induced in the blood of asthmatic children with additional Gram + bacteria in the nasopharynx (Gr+/-). Furthermore, asthmatic children had more episodes of infection that required antibiotic therapy than the control group. Treatment with antibiotics associated with reduced ST2 in blood cells of both asthmatic and control children and reduced IL-33 levels in the airways of asthmatic children. In the absence of Staphylococcus (S.) aureus in NPF, antibiotic therapy associated with decreased IL-33 levels in the NPF and lower ST2 values in the blood of control children but not of asthmatic children. These data suggest that, in asthmatic children, Gram- bacteria, which persist after antibiotic therapy, contributes to IL-33 locally and associated with Gr + bacteria colonization in the airways, inhibited IFN-? and in the absence of Staphylococcus (S.) aureus, induced ST2 bearing cells in their blood.
EVALuna2:7728